Adjuvant systemic therapy of gastrointestinal stromal tumors: The Scandinavian Sarcoma Group perspective. - Joensuu H; Eriksson M (Acta Orthopaedica (Supplement))
Gastrointestinal stromal tumors (GISTs) have a malignant potential varying from virtually no risk of recurrence (microscopic GISTs) to a high risk. Acquired secondary mutations that interfere with imatinib binding have been identified as a common mechanism for drug resistance and tumor progression in advanced GIST. Patients with advanced GIST but with a small tumor mass have the longest time to disease progression suggesting that the rate of secondary mutations that confer drug resistance may be low when the number of cancer cells is small. Thus, early administration of imatinib in the adjuvant setting might result in a low rate of secondary mutations and might improve survival. The results of the ACOSOG Z9001 trial demonstrated a significantly longer recurrence-free survival among patients treated with adjuvant imatinib as compared to placebo. Although data on influence of adjuvant imatinib on overall survival is lacking, its administration may be warranted to patients who have a high risk of recurrence and death from GIST that likely exceeds the risks related to adjuvant administration of imatinib. Many aspects of adjuvant treatment remain unknown including the overall benefits and harms of adjuvant treatment, optimal selection of patients for treatment, and the duration of adjuvant treatment, which is currently being investigated in the ongoing Scandinavian Sarcoma Group/AIO trial (SSG/AIO XVIII).